Study Literatur Pengembangan Media Pembelajaran Pocket Book Matematika SD Materi Perkalian, Pembagian dan Mata Uang Kelas II - Dwi Retno Trisniani; Chelsea Meida Putri Indianto; Fierly Nadia Rahmadina; Nayla Aulia Pratiwi; Gizka Chesilia Ardiwilaga; Sri Duik Astatik (Prosiding Konferensi Ilmiah Dasar, 2026)
Mathematics education in elementary schools often encounters challenges due to the abstract nature of mathematical concepts, particularly in multiplication, division, and money-related topics. This study aims to describe the characteristics of the development of the Mathematics Pocket Book learning media and to analyze its feasibility and effectiveness based on findings from previous studies. The study employed the Systematic Literature Review (SLR) method using a qualitative descriptive content analysis approach. Data were collected from journal articles, conference proceedings, and other scholarly publications indexed in Google Scholar, Garuda, and SINTA, published between 2020 and 2026. The findings indicate that the Mathematics Pocket Book was developed through several stages, including needs analysis, design, development, expert validation, field testing, and revision. The media was found to be feasible for use based on validation results from subject matter experts, media experts, and language experts, and it received highly positive responses from students in both small-group and large-group trials. Furthermore, the Mathematics Pocket Book was shown to enhance students' learning motivation, facilitate conceptual understanding, and support independent learning in multiplication, division, and money topics. Therefore, the Mathematics Pocket Book is considered feasible, practical, and effective for use in Grade II elementary mathematics learning. Future research is recommended to employ Research and Development (RD) or experimental methods to evaluate the media's effectiveness through direct implementation.